THE EFFECT OF FISHING LINE ARRANGEMENT OF TROLLING LINE ON CATCHES IN TANJUNG MUTIARA SUB-DISTRICT AGAM DISTRICT WEST SUMATRA PROVINCE - Zaimi Aulia Sandy; Bustari Bustari; Ronald M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe study was conducted on April 2018 in Tanjung Mutiara sub-district, Agam regency, West Sumatera Province. This study aims to see the effect of the fishing line arrangement on the catches of trolling line. The method used in this study is a experimental and research conducted during 5 days of arrest. The catch during the study was 5059 fishes. The catch consists of one species. Keywords: Trolling line, Catch, Tanjung Mutiara District